Factors Affecting New Firm Success and Their Use in Venture Capital Financing - Timothy Bates; William D. Bradford (Journal of Small Business Finance, 1992)
Using a nationwide sample of 14,424 new firms, we find that attractive human capital traits at business entry for entrepreneurs include high educational attainment, owners who lie in the middle of—as opposed to the tails of—the age distribution, and family business background. Attractive firm traits are purchase of an existing firm rather than starting a firm de novo, and larger amounts of starting capital. Recent research has found that certain ethnic minorities are differentially restricted from obtaining commercial bank financing. Our statistical tests indicate that when we control for differences in human capital and firm traits, the venture capital market also differentially restricts minority entrepreneurs from obtaining venture capital. Thus public policy seeking to reduce the resulting financing gap for minority entrepreneurs may have economic justification. Except for the ethnic trait, the venture capital market's use of owner and firm information is consistent with selecting those firms which have more survival potential.
Keywords: G24; L25; M13; 650; New Firm; Success; Venture Capital